A quantum dot intercalated robust covalent organic framework membrane for ultrafast proton conduction. Issue 12 (21st February 2022) - Fan, Chunyang; Peng, Quan; Wu, Hong; Shi, Benbing; Wang, Xiaoyao; Ye, Chumei; Kong, Yan; Yin, Zhuoyu; Liu, Yiqin; Jiang, Zhongyi
Abstract : A phosphorylated GQD intercalated COF membrane simultaneously exhibits superhigh proton conductivity and outstanding mechanical strength. Abstract : Proton exchange membranes (PEMs) integrating high proton conductivity and exceptional mechanical properties are desirable for numerous energy-related fields. Here, a zero-dimensional (0D) graphene quantum dot (GQD) functionalized with phosphoric acid groups was intercalated into two-dimensional (2D) sulfonated COF nanosheets to fabricate robust PEMs. The optimal GQD-intercalated COF membrane exhibits superior proton conductivity at both high and low relative humidities (0.923 and 0.096 S cm −1 at 90 °C, 100% and 40% relative humidity, respectively) and a high tensile strength of ∼129 MPa, greatly surpassing the state-of-the-art PEMs. These unprecedented properties mainly stem from the ultrahigh density and regular arrangement of proton carriers in the long-range ordered proton conductive channels as well as multiple interactions including π–π interactions and electrostatic interactions between the functionalized GQDs and sulfonated COF nanosheets. This 0D/2D co-assembled strategy offers an efficient and facile way for the development of robust and high-performance membranes appealing to various applications.